ANALISIS TINGKAT KEBANGKRUTAN PADA PERUSAHAAN RITEL SEKTOR SANDANG YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020 - Eka Yudhyani; Camelia Verahastuti; Ratna Dian Sari (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2022)
Running a business in the Retail sector in the Clothing Sector is very risky for bankruptcy, therefore it is necessary to use an analytical tool that 95% can produce accurate and reliable results such as the Altman Z-Score, in order to easily predict the level of bankruptcy in the company. This study examines retail companies in the clothing sector by taking 3 samples from the sector companies. This study aims to determine: the bankruptcy of PT. Matahari Department Store Tbk, PT. Mitra Adiperkasa Tbk and PT. Ramayana Lestari Sentosa Tbk as a Retail Company in the Clothing Sector Listed on the Indonesia Stock Exchange in 2018-2020. The hypothesis is accepted this is due to the phenomenon of the problem of the start of the shopping boom online and there is also a COVID-19 pandemic lockdown in 2020, and the fierce competition factor, the lack of employees or workers and increasingly sophisticated technological factors make businessmen in the retail sector of the clothing sector experience the potential for bankruptcy